(untitled) (CIPEEX, 2025)
The sterilization of Escherichia coli (E. coli) represents a significant challenge in Medicine and the food industry, due to the potential for infection and disease spread. Traditional methods such as antibiotics and chemical disinfectants have limitations due to bacterial resistance and adverse effects. This manuscript reviews the use of biophotonic therapies as innovative alternatives for the inactivation of E. coli. The biophotonic approach uses light at specific wavelengths, associated with photosensitizing agents, to induce bacterial cell death. The study explores sterilization protocols based on laser, photodynamic therapy (PDT), and light-emitting diodes (LEDs), analyzing mechanisms of action, application parameters, and advantages compared to traditional methods. The methodology included the analysis of articles published in the last 10 years in the PubMed database, focusing on the sterilization of E. coli using biophotonic techniques, with descriptors such as "sterilization," "E. coli," "Laser," and "biophotonic therapy." The results highlight the effectiveness of different approaches. The use of methylene blue (MB) and sodium bicarbonate showed bactericidal effects, but with limitations; polymeric nanoparticles conjugated with croconaine (CR-PQAC) demonstrated efficacy under NIR light; curcumin proved promising for preserving food while maintaining sensory quality; and photodynamic therapy (aPDT) was comparable to conventional chemical disinfectants. With this literature review, it can be concluded that biophotonic technologies are effective in inactivating E. coli and offer ecological and efficient alternatives for microbial control.